Macroeconomics : a contemporary introduction - Robinson, T. J. C. (Tim J. C.), 1945-; Quayle, Michael; McEachern, William (South Melbourne : Nelson, 1994)
This book is divided into four parts: Introduction to economics; Fundamentals of macroeconomics; Fiscal and monetary policy; and The international setting.
Keywords: Australia; Economics; Macroeconomics; Australia -- Economic conditions; Macroeconomics